Religious pluralism assessed - Sagi, Avi (Sophia, 1999)
Exclusivism is a highly appealing option in religious terms. It reflects the believers’ commitment to their religion as well as their conviction that their religion is true, and that other religions are therefore false., My central argument is that the justification of inter-religious pluralism, while not less well established than that of exclusivism, successfully preserves the social intuitions of religious devotion and commitment. The effect of this justification, which remains valid despite objections raised against various forms of inter-religious pluralism, is to undermine exclusivism.